The Role of Client-Contractor Relationship in Solving Financing Failure in Construction Project: Case Study - Augustinus Simanjuntak; Hotlan Siagian (Petra International Journal of Business Studies, 2023)
The construction industry supply chain emphasizes the importance of the client and contractor relationship. This research examines the process of evaluating the Contractor's capability in selecting a contractor. This study also reviews how the project owner solves the problem during work. This research uses a qualitative and case study approach. The study is based on library research, the Delphi method, and content analysis. The results of the study show: (a) in building a relationship, PT XYZ and the Contractor has declared about its business legal documents to the ABC institution; (b) However, in building a relationship, PT XYZ was not transparent about its financial capabilities and business ownership structure; (c) PT XYZ's failure to finance the project has disrupted the relationship of the two parties; (d) PT XYZ (Contractor) has declared about its financial failure; (d) the ABC institution overcomes it with a relationship beyond contract model, which is first to bail out the Contractor's finances so that PT XYZ can still carry out the construction service contract to completion. The ABC institution decided to bail out PT.XYZ is primarily based on the values practiced by the ABC institution, known as LIGHT, which means Love, Integrity, Growth, Humanity, and Trust.